Analysis of Excess Energy Production in Hybrid Vertical Axis Wind Turbine-Solar Cell di Jalan Tol Sayung Demak - Kurniawan, Nanang Candra (Mestro: Jurnal Teknik Mesin dan Elektro, 2024)
This study analyzes the excess production of electrical energy from a hybrid system combining a 500W vertical axis wind turbine and 2 x 250W solar panels implemented on the Demak-Semarang Toll Road. The system is designed to meet the electricity needs of toll road infrastructure, particularly for lighting and traffic monitoring. Wind speed and solar radiation data were collected using NASA's LARD (Langley Atmospheric Research Data) from January to December 2023. The calculation method used involves linear interpolation on the wind turbine power curve and the calculation of solar panel output power based on panel area and hourly solar radiation. The analysis results show that the hybrid system generates a total energy of 2662.93 Wh per day, while the lighting load requires 1680 Wh per day. Thus, there is an excess energy production of 982.93 Wh per day. This surplus energy can be stored in a 24V 90Ah LiFePO4 battery for use during periods of low energy production or at night. The excess energy production varies each month, with the highest peak occurring in February (46.296 kWh) and the lowest in April (15.793 kWh). This hybrid system not only improves the reliability of the energy supply but also reduces dependence on conventional grid electricity. The study demonstrates that the hybrid system of vertical axis wind turbines and solar panels is an effective and sustainable solution for meeting energy needs in transportation infrastructure, particularly on toll roads. The results of this study are expected to serve as a reference for further development in the implementation of renewable energy in the transportation sector.